A fluorescent probe for detection homocysteine in green and NIR, and cysteine/glutathione in NIR regions. (21st December 2021) - Zhang, Shuwei; Xia, Qianwen; Wang, Fei; Wang, Ting; Jia, Xiaodong; Yuan, Yu; Zhang, Min; Chen, Gang
Graphical abstract: A fluorescent probe (NBD-XA ) containing benzoxadiazole and xanthen moieties was designed and synthesized to detect Hcy in green and NIR, and Cys/GSH in NIR regions, whose detection mechanism was based on the nucleophilic aromatic substitution reaction between the fluorescent probe and sulfhydryl of biothiols, and the following different rearrangement reactions for biothiols. Meanwhile, NBD-XA exhibited low cytotoxicity, and was successfully applied for bioimaging in living cells. Abstract: A fluorescent probe (NBD-XA ) containing benzoxadiazole and xanthen moieties was designed and synthesized to detect homocysteine (Hcy) in green and near infrared (NIR), and cysteine/glutathione (Cys/GSH) in NIR regions, whose detection mechanism was based on the nucleophilic aromatic substitution reaction between the fluorescent probe and sulfhydryl of biothiols, and the following different rearrangement reactions for these biothiols. Meanwhile, NBD-XA exhibited low cytotoxicity, and was successfully applied for bioimaging in living cells.